Physicochemical And Biological Characterization Of Vermicompost Prepared From Different Residues Of Agroforestry Component (Applied Biological Research, 2019)
The present study was conducted in the year 2018-19 at DBSKKV, Dapoli,  Maharashtra (India) with aim to physico-chemically and biologically  characterize the vermicomposts prepared from the residues obtained from different agroforestry sources. Eisenia foetida was used in vermicomposting.  The residues of 14 easily available agroforestry plant species were collected  and prepared in different randomized blocks. Among the various species  evaluated, Megathyrsus maximus, Eluecine coracana, Themenda species,  Setaria sphacelata, Gmelina arborea and Termenelia tomentosa proved  significantly superior in yielding higher and enriched vermicompost.  Maximum decomposition during partial decomposition study for 120 days  was observed in cereal and grass species. The 20 released earthworms in each  treatment showed a population of 876.5 and 646.5 in M. maximus and O. sativa residues. The maximum recovery of vermicompost was observed in Bridelia retusa, T. tomentosa, M. maximus and S. sphacelate. Significant  improvements in colour and bulk density were noticed in cereal, grass and  nutritious plantation species (T. tomentosa). Maximum improvement in some  physicochemical characteristics [pH, EC, OC, available NPK, total NPK] and  microbial activities [CO2 evolution and bacterial, actinomycete and fungal  populations] were observed in easily decomposed and nutritious species (T. tomentosa, G. arborea). Significantly high dehydrogenase activity, soil  microbial biomass carbon and nitrogen, total N, total C and C:N ratio were  observed in M. maximus, E. coracana, G. arborea and T. tomentosa. These  species are recommended for producing quality vermicompost and its  production on the farmers field.
Keywords: Bacteria; C:N ratio; CO2; colour; dehydrogenase; vermi composting